(untitled) (Research, Society and Development, 2020)
Pregnancy is a physiological process understood by the sequence of adaptations in the woman’s body from fertilization to birth, which, being a physiological characteristic of the woman, her reproductive functions require an intensification and adaptation of the body’s metabolic and physiological processes accordingly with fetal growth. This research is an integrative literature review that seeks to demonstrate the importance of the physiotherapist during the gestational period and the postpartum period. The physiotherapist should guide the patient in general, as to a correct adaptation to the bed, about early walking, how to avoid analgesic postures, consequently reducing muscle tension promoting analgesia, providing physical comfort, individualized care, attention to their needs. It is concluded through the results obtained in the present study, that the physiotherapist has an important action both in the gestational period and in the postpartum period, since the physiotherapist when integrated in the multidisciplinary team, acts directly in the family planning, to carry out obstetric monitoring.